Scrutinizing Coronaviruses Using Publicly Available Bioinformatic Tools: The Viral Structural Proteins as a Case Study - Beeckmans, Sonia; Van Driessche, Edilbert (Frontiers in Molecular Biosciences, 2021)
Since early 2020, the world suffers from a new beta-coronavirus, called SARS-CoV-2, that has devastating effects globally due to its associated disease, Covid-19. Until today, Covid-19, which not only causes life-threatening lung infections but also impairs various other organs and tissues, has killed hundreds of thousands of people and caused irreparable damage to many others. Since the very onset of the pandemic, huge efforts were made worldwide to fully understand this virus and numerous studies were, and still are, published. Many of these deal with structural analyses of the viral spike glycoprotein and with vaccine development, antibodies and antiviral molecules or immunomodulators that are assumed to become essential tools in the struggle against the virus. This paper summarizes knowledge on the properties of the four structural proteins (spike protein S, membrane protein M, envelope protein E and nucleocapsid protein N) of the SARS-CoV-2 virus and its relatives, SARS-CoV and MERS-CoV, that emerged few years earlier. Moreover, attention is paid to ways to analyze such proteins using freely available bioinformatic tools and, more importantly, to bring these proteins alive by looking at them on a computer/laptop screen with the easy-to-use but highly performant and interactive molecular graphics program DeepView. It is hoped that this paper will stimulate non-bioinformaticians and non-specialists in structural biology to scrutinize these and other macromolecules and as such will contribute to establishing procedures to fight these and maybe other forthcoming viruses.